2009
DOI: 10.1016/j.scr.2009.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Human embryonic stem cell-derived mesenchymal progenitors—Potential in regenerative medicine

Abstract: Tissue engineering and cell therapy require large-scale production of homogeneous populations of lineage-restricted progenitor cells that easily can be induced to differentiate into a specific tissue. We have developed straightforward protocols for the establishment of human embryonic stem (hES) cell-derived mesenchymal progenitor (hES-MP) cell lines. The reproducibility was proven by derivation of multiple hES-MP cell lines from 10 different hES cell lines. To illustrate clinical applicability, a xeno-free hE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
116
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(125 citation statements)
references
References 25 publications
5
116
0
2
Order By: Relevance
“…4). We conclude that iPS-and ES-MSCs displayed a greater propensity to undergo osteogenic and chondrogenic differentiation than adipogenic differentiation, and in this respect, our results resemble findings reported in ESC-derived MSCs [13,19,33], fetal, and other gestational product-derived MSCs [2, 5, 34 -38].…”
Section: Stem Cells Translational Medicinesupporting
confidence: 84%
See 1 more Smart Citation
“…4). We conclude that iPS-and ES-MSCs displayed a greater propensity to undergo osteogenic and chondrogenic differentiation than adipogenic differentiation, and in this respect, our results resemble findings reported in ESC-derived MSCs [13,19,33], fetal, and other gestational product-derived MSCs [2, 5, 34 -38].…”
Section: Stem Cells Translational Medicinesupporting
confidence: 84%
“…Similarly, primary deciduoplacental MSCs [34], umbilical cord blood [38], Wharton's jelly [35,36], and fetal MSCs [37,56] have been reported to have less adipogenicity than adult bone marrow MSCs. Consistent with this, the ESC-derived MSC literature to date either reports cells displaying low adipogenesis [13,19,33] or avoids commenting on relative adipogenic capability [8 -10, 12, 14, 16]. There are few reports as yet of iPS-MSCs, although Zhang et al performed a semiquantitative analysis of adipogenic and osteogenic differentiation to claim that differentiation was similar in bone marrow MSCs, fetal MSCs, and ES-and iPS-derived MSCs [57].…”
Section: Discussionmentioning
confidence: 92%
“…This issue may eventually be much better addressed by pluripotent stem cell derivatives. At this point, in addition to basal keratinocytes, protocols are available for differentiation into melanocytes (unpublished data and [33]) and fibroblasts [34], mesenchymal stem cells [35], and adipocytes [36] that can be introduced into the final cell therapy product to improve its overall quality.…”
Section: What Can Pluripotent Stem Cells Do For Our Skin Beyond Keratmentioning
confidence: 99%
“…Also, our preliminary data showed hESCs derived MSCs (hESCs-MSCs) with fibroblast-like morphology ( Figure 1) expressed CD105 and FIBRONECTIN as MSC specific markers (unpublished data; Figure 1). Karlsson et al [12] used Xeno-free derivation of MSCs from hESCs as an optimal protocol for the first time and reported these cells with MSCs phenotype and differentiation potential into mesodermal tissues do not form teratomas when transplanted under the kidney capsule of severe combined immunodeficiency (SCID) mice [12]. Similar to these potential, reports demonstrated that hESCs-MSCs not only were phenotypically similar to bone marrow derived MSCs (BM-MSCs) and adipose derived MSCs (AMSCs), but also, showed higher in vitro proliferation capacity and equivalent differentiation potential into adipocytes and osteocytes [13].…”
Section: Introductionmentioning
confidence: 99%